Identification and Screening of Natural Neuraminidase Inhibitors from Reduning Injection via One-Step High-Performance Liquid Chromatography-Fraction Collector and UHPLC/Q-TOF-MS - Lijun An; Xie-An Yu; Wei Liu; Jin Li; Yan-Xu Chang (International Journal of Analytical Chemistry)
Neuraminidase plays an essential role in the spread of influenza viruses via cleaving sialic acids from the host cell receptors and virions. Neuraminidase has been regarded as an essential target for prevention and treatment of influenza infection. The one-step high-performance liquid chromatography-fraction collector (HPLC-FC) was selected to prepare fractions from Reduning (RDN) injection, while ultra-high-performance liquid chromatography/quadrupole-time-of-flight mass spectrometry (UHPLC/Q-TOF-MS) was used to identify fractions depending on their retention time and molecular ion. As a result, 75 fractions were prepared and 28 fractions out of them exhibited NA inhibitory effects with the dose-effect relationship. Exploring it further, six components including neochlorogenic acid, chlorogenic acid, cryptochlorogenic acid, isochlorogenic acid B, isochlorogenic acid A, and isochlorogenic acid C were the main components that accounted for almost 80% of inhibitory activity of RDN injection. Accordingly, these results demonstrated that this strategy could not only rapidly identify but also accurately screen active components from traditional Chinese medicine.